Tapping eavesdropper designs against physical layer secret key in point-to-point fiber communications - Hu, Wenxiu; Wei, Zhuangkun; Popov, Sergei; Leeson, Mark; Xu, Tianhua (IEEE, 2022)
With the growing demand for service access and data transmission, security issues in optical fiber systems have become increasingly important and the subject of increased research. Physical layer secret key generation (PL-SKG), which leverages the random but common channel properties at legitimate parties, has been shown to be a secure, low-cost, and easily deployed technique as opposed to computational-based cryptography, quantum, and chaos key methods that rely on precise equipment. However, the eavesdropper (Eve) potential for current PL-SKG in fiber communications has been overlooked by most studies to date. Unlike wireless communications, where the randomness comes from the spatial multi-paths that cannot be all captured by Eves, in fiber communications, all the randomness (from transmitted random pilots or channel randomness) is contained in the signals transmitted inside the fiber. This, therefore, enables a tapping Eve to reconstruct the common features of legitimate users from its received signals, and further decrypt the featured-based secret keys. To implement this idea, we designed two Eve schemes against polarization mode distortion (PMD) based PL-SKG and the two-way cross multiplication based PL-SKG. The simulation results show that our proposed Eves can successfully reconstruct the legitimate common feature and the secret key relied upon, leading to secret key rate (SKR) reductions of between three and four orders of magnitude in the PL-SKG schemes studied. As a result, we reveal and demonstrate a novel eavesdropping potential to provide challenges for current physical layer secret key designs. We hope to provide more insightful vision and critical evaluation on the design of new physical layer secret key schemes in optical fiber links, to provide more comprehensively secure, and intelligent optical networks.
Keywords: fiber communications; fiber tapping; eavesdropping; physical layer security; secret key generation